2019
DOI: 10.1007/s11240-019-01731-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling of different tissues from beta-carotene-enhanced transgenic soybean and its non-transgenic counterpart

Abstract: Beta-carotene-enhanced transgenic soybeans, harboring genes encoding phytoene synthase and carotene desaturase under the control of a seed-specific promoter, were developed to alleviate vitamin A deficiency in populations, the diet of which was deficient in this vitamin. However, metabolic engineering of carotenoid biosynthetic pathways often has unintended effects, leading to major metabolic changes in plants that harbor endogenous beta-carotene biosynthesis pathways. In the present study, we performed transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Additionally, the overexpression of LCYb gene in tomato resulted in the enhanced metabolism of lycopene to β-carotene and in the increase of ABA content what was linked with extended fruit shelf life [ 9 ]. Gene ontology analysis revealed that several genes involved in cell wall organisation and hydrolase activity of O -glycosyl compounds were upregulated also in soybean containing the insertion of psy overexpressing construct [ 10 ]. The yellow-fruited tomato 1 ( yft1 ) mutant, which fruit contained only 6% of the total carotenoids of that of the wild type cultivar, had delayed chromoplast development and a modified cell wall composition [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the overexpression of LCYb gene in tomato resulted in the enhanced metabolism of lycopene to β-carotene and in the increase of ABA content what was linked with extended fruit shelf life [ 9 ]. Gene ontology analysis revealed that several genes involved in cell wall organisation and hydrolase activity of O -glycosyl compounds were upregulated also in soybean containing the insertion of psy overexpressing construct [ 10 ]. The yellow-fruited tomato 1 ( yft1 ) mutant, which fruit contained only 6% of the total carotenoids of that of the wild type cultivar, had delayed chromoplast development and a modified cell wall composition [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed for the first time that alterations in carotenoid biosynthesis are related to cell wall remodelling, which was visualised directly in the cell walls with the use of immunohistochemistry method. Furthermore, some changes in gene expression and protein synthesis in soybean that were connected to carotenoid biosynthesis were detected for fascilin-like AGP [ 10 ]. Our study presents another data that indicate a correlation between AGPs presence and carotene biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Recently, a comparative transcriptomic profiling showed enriched transcripts of six GELPs in selected β-carotene-enhanced soybean stems, leaves, and seeds. 68 The exact mechanism of why these GELPs are overproduced in this transgenic soybean still remains unknown.…”
Section: Soybean (Glycine Max)mentioning
confidence: 99%
“…This variety was created from modified Kwangan variety soybean to produce higher amounts of β‐carotene, a precursor of vitamin A 67 . Recently, a comparative transcriptomic profiling showed enriched transcripts of six GELP s in selected β‐carotene‐enhanced soybean stems, leaves, and seeds 68 . The exact mechanism of why these GELPs are overproduced in this transgenic soybean still remains unknown.…”
Section: Soybean (Glycine Max)mentioning
confidence: 99%